Qur’anic Manuscripts, Mythmaking, and the Cultural Economy in Madura - Rohmah, Ifa Faizah; Cece, Cece; Nurkhalis, Nurkhalis; Gussevi, Sofia (Postgraduate Studies of UIN Sunan Ampel Surabaya, Indonesia, 2025)
This study explores how sacred Qur’anic manuscripts in Madura, Indonesia, are embedded in local mythological narratives and transformed into cultural and economic resources. Although these manuscripts are preserved as religious artifacts, they also function as “living texts” that circulate meaning and power within spiritual, cultural, and touristic contexts. The research aims to examine how local myths surrounding these manuscripts mediate between faith, authority, and contemporary cultural tourism. Using a qualitative approach that includes participant observation and semi-structured interviews with manuscript custodians, religious leaders, and visitors, the study analyzes how stories of miraculous origins—such as manuscripts written in one night or underwater—shape public perception and enhance symbolic value. The findings reveal that these narratives serve not only as expressions of belief but also as strategies of cultural preservation and commodification, turning sacred texts into heritage objects that attract visitors and generate community pride. The study contributes to a broader understanding of how religious heritage in Muslim societies is continually reinterpreted through narrative, economy, and local identity.